Two new and one newly recorded gonad-infecting species of Philometra Costa, 1845 (Nematoda: Philometridae) parasitising marine fishes in Iraq - Moravec, František; Fazaa, Hassan A; Ali, Atheer H; Saud, Hussein A (Systematic parasitology, 2023)
Specimens of two undescribed and one known gonad-infecting species of Philometra Costa, 1845 (Nematoda: Philometridae) were collected in some marine fishes from off the southern coast of Iraq. Based on light and scanning electron microscopy, the following new species are described: Philometra tayeni n. sp. (males and nongravid females) from ovaries of the purple-spotted bigeye Priacanthus tayenus Richardson (Priacanthidae, Acanthuriformes), and Philometra nibeae n. sp. (males and gravid female) from the ovary of the blotched croaker Nibea maculata (Bloch et Schneider) (Sciaenidae, Acanthuriformes). Philometra tayeni is mainly characterised by a pair of postanal papillae and a V-shaped caudal mound in males and by their body lengths (2.42-2.99 mm), whereas P. nibeae differs from its gonad-infecting congeners parasitising scienids mainly based on the body length of males (2.29-2.49 mm) and their spicules (96-117 µm), absence of a pair of postanal papillae and shape of caudal mound consisting of two parts. Philometra piscaria Moravec & Justine, 2014 (males and nongravid females), a parasite of the orange-spotted grouper Epinephelus coioides (Hamilton) (Epinephelidae, Perciformes), is recorded from the Arabian (= Persian) Gulf for the first time; previously unknown females of this species are described.
Keywords: Microscopy, Electron, Scanning; Dracunculoidea; Percoidea; mikroskopie elektronová rastrovací; Bass; Iraq; mužské pohlaví; Irák; Nematoda; Gonads; gonády; ženské pohlaví; zvířata; nemoci ryb; Species Specificity; hlístice; Fish Diseases; Fishes; Perciformes; druhová specificita; ryby; Female; Male; Animals